(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The idea of digital technology has gone global and has transformed the nature of entrepreneurship thus leaving the old ways of running the business different. This paper examines the digital entrepreneurship in India. It looks at the interaction between the programs of the government like the Digital India, the new technology as well as the rising gig market. Reviewing such companies, as Zerodha, Nykaa, Zomato, and PhysicsWallah, the study highlights such key success factors as low costs growth and targeting local customers, yet the presence of structural issues, which remain in place. It also examines innovative strategies that could assist these companies to remain robust whenever there is a shift in the market.